1995
DOI: 10.1101/gad.9.10.1250
|View full text |Cite
|
Sign up to set email alerts
|

GATA-1 reprograms avian myelomonocytic cell lines into eosinophils, thromboblasts, and erythroblasts.

Abstract: The transcription factor GATA-1 is expressed in early hematopoietic progenitors and specifically down-regulated in myelomonocytic cells during lineage determination. Our earlier observation that the differentiation of Myb-Ets-transformed chicken hematopoietic progenitors into myeloblasts likewise involves a GATA-I down-regulation, whereas expression is maintained in erythroid, thrombocytic, and eosinophilic derivatives, prompted us to study the effect of forced GATA-I expression in Myb--Ets-transformed myelobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
312
2
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(331 citation statements)
references
References 61 publications
15
312
2
2
Order By: Relevance
“…Further studies revealed the multipotential nature of these transformed progenitor cells Moscovici et al, 1983a,b). Cell lines derived from these E26-transformed progenitors have proven very useful in dissecting the regulation of hematopoietic di erentiation (Kulessa et al, 1995;Rossi et al, 1996). Temperature-sensitive variants of the E26 virus have been isolated and molecularly characterized (Beug et al, 1984).…”
Section: Cells and Transformation Assays (Figure 2)mentioning
confidence: 99%
“…Further studies revealed the multipotential nature of these transformed progenitor cells Moscovici et al, 1983a,b). Cell lines derived from these E26-transformed progenitors have proven very useful in dissecting the regulation of hematopoietic di erentiation (Kulessa et al, 1995;Rossi et al, 1996). Temperature-sensitive variants of the E26 virus have been isolated and molecularly characterized (Beug et al, 1984).…”
Section: Cells and Transformation Assays (Figure 2)mentioning
confidence: 99%
“…The promiscuous expression of these lineage-specific markers has so frequently been observed in hematopoietic malignancies [5,6] that it is considered a hallmark of leukemia [5]. Furthermore, the switch between erythroid and myeloid lineages has also been reported on some transformed hematopoietic [7][8][9] and leukemic [10][11][12] cell lines. Taken together, these studies suggest that erythroid and myeloid development are closely associated in both normal hematopoiesis and hematopoietic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Enforced expression of transcriptional factors such as GATA-1 and PU.1 leads to the lineage switch of myeloid cells to cells with another myeloid phenotype. [12][13][14][15][16][17] These lineage switches include myeloid to megakaryocytic, myeloid to eosinophilic, myeloid to erythroid, and erythroid to myeloid conversions. The ectopic expression of PU.1 and C/EBP also results in the commitment of hematopoietic progenitors to an eosinophilic lineage.…”
Section: Introductionmentioning
confidence: 99%